1975
DOI: 10.1002/cjce.5450530407
|View full text |Cite
|
Sign up to set email alerts
|

Particle segregation in a fluidized bed

Abstract: Particle segregation data at low gas velocity, near the minimum fluidizing velocity, are presented for particles of different size (150 to 2800 μm) and density (720 to 2800 kg/m3) in a fluidized bed. Phase diagrams similar to those of liquid‐solid systems are developed to present the results. The data were collected in a 100 mm diameter unit operating at pressures up to 660 kPa and a 114 mm diameter unit at atmospheric pressure. The particle segregation data were obtained to provide design and operating criter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
46
0

Year Published

1982
1982
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(48 citation statements)
references
References 4 publications
2
46
0
Order By: Relevance
“…This will increase the possibility of particle segregation. The study on particle segregation conducted by the Westinghouse Electric Corporation in fluidized beds containing dolomite and char particles showed the occurrence of segregation in most situations, when the gas velocity was lowered [38]. Hence it is possible that once agglomeration is initiated by low melting particles, such as those of the SG4 density class, the change in bed hydrodynamics would lead to further agglomeration due to decreasing particle velocities and decreasing bed voidage.…”
Section: Implications To Bed Ash Agglomerationmentioning
confidence: 99%
“…This will increase the possibility of particle segregation. The study on particle segregation conducted by the Westinghouse Electric Corporation in fluidized beds containing dolomite and char particles showed the occurrence of segregation in most situations, when the gas velocity was lowered [38]. Hence it is possible that once agglomeration is initiated by low melting particles, such as those of the SG4 density class, the change in bed hydrodynamics would lead to further agglomeration due to decreasing particle velocities and decreasing bed voidage.…”
Section: Implications To Bed Ash Agglomerationmentioning
confidence: 99%
“…As the gas flow rate is increased, it moves across the bed down to the bottom of the column until, at a new characteristic velocity value, the whole bed is brought into a fully fluidized state. In the upper region of the bed, at its free surface, a bubbling layer builds up which contains almost exclusively one of [3,4,5]. They are the "initial f luidization velocity", u if , at which ∆p first deviates from the fixed bed curve, and the "final f luidization velocity", u f f , at which the ultimate value of ∆p is first attained.…”
Section: The Essential Features Of Binar Y Fluidizationmentioning
confidence: 99%
“…Based on this, it is u f f , rather than u mf , that has to be viewed as the velocity at which the entire mixture attains the f luidized condition [3][4][5]9]. This velocity normally coincides with that of full mixing [10], while the difference between u f f and u if is the amplitude of the velocity range within which mixing/segregation phenomena occur [20].…”
Section: A Clearer Approach To Binar Y Fluidizationmentioning
confidence: 99%
“…On the pressure drop versus gas velocity diagram, uif is located at the point p first deviates from the fixed bed trend, whereas uff is the velocity at which the ultimate value of p is attained. The pioneering studies of Chen and Keairns [1], Gelperin and Einstein [2] and Vaid and Sen Gupta [3] first revealed that fluidization of binary and ternary beds is a process that has place gradually. More recently, the dependence of both uif and uff on the main variables which determine the fluidization pattern (solid properties, mixture composition and bed geometry) has been investigated by Formisani et al [4][5][6], who analyzed the behaviour of a large number of twocomponent mixtures.…”
Section: Introduction and Previous Workmentioning
confidence: 99%